2012
DOI: 10.1167/12.6.34
|View full text |Cite
|
Sign up to set email alerts
|

Privileged visual processing of the straight-ahead direction in humans

Abstract: At any moment, the objects we face are endowed with a special behavioral status, either as potential obstacles during navigation or as optimal targets for visually guided actions. Yet, the gaze frequently jumps from one location to another when exploring the visual surroundings, so that objects located straight-ahead are often seen from the corner of the eyes. In the present study, we tested the hypothesis that peripheral vision might nevertheless ensure a privileged processing of these behaviorally important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 56 publications
3
26
1
Order By: Relevance
“…The presence of eye position signals in these areas supports this view 2, 37-39 . Similarly, our conclusions are compatible with other purported roles for eye-position information in V1, including the prioritization of visual signals arising from directly in front of an observer's body 3,40 , and the stabilization of image representations during fixational eye movements [41][42][43][44] .…”
Section: Discussionsupporting
confidence: 89%
“…The presence of eye position signals in these areas supports this view 2, 37-39 . Similarly, our conclusions are compatible with other purported roles for eye-position information in V1, including the prioritization of visual signals arising from directly in front of an observer's body 3,40 , and the stabilization of image representations during fixational eye movements [41][42][43][44] .…”
Section: Discussionsupporting
confidence: 89%
“…Another possibility is that the visual map incoporates oculoproprioception, so that a distortion of this signal causes a systematic error in locating visual targets relative to the body. Visual stimuli presented nearer the hand (Reed, Grubb, & Steele, 2006), the head midline (Durand, Camors, Trotter, & Celebrini, 2012;Durand, Trotter, & Celebrini, 2010), or the trunk midline (Grubb, Reed, Bate, Garza, & Roberts, 2008) have a privileged access to neural processing resources compared with visual stimuli presented elsewhere. A mislocalization of the visual stimuli relative to these landmarks could, in our previous studies, have changed their neural processing priority.…”
Section: Introductionmentioning
confidence: 99%
“…The two experiments differed solely in the locations of the stimuli. In the first experiment, we followed the experimental design of our previous behavioral study (Durand et al 2012) and the stimulus was presented along the horizontal meridian (i.e. at eye level) at 10° of eccentricity either to the left or to the right of ocular fixation (Fig.…”
Section: Stimulimentioning
confidence: 99%
“…In humans, a growing body of evidences also suggests that the straight-ahead direction benefits from a privileged processing in peripheral vision. Behavioral studies (Camors et al 2016;Durand et al 2012) showed that participants react faster to visual stimuli if they are located straight-ahead rather than in an eccentric position, even if their visual properties (i.e. their retinal images) are strictly identical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation